Successful management of Halyomorpha halys (Hemiptera: Pentatomidae) in commercial apple orchards with an attract‐and‐kill strategy. Issue 1 (21st September 2018) - Morrison, William R; Blaauw, Brett R; Short, Brent D; Nielsen, Anne L; Bergh, James C; Krawczyk, Greg; Park, Yong‐Lak; Butler, Bryan; Khrimian, Ashot; Leskey, Tracy C
Abstract: BACKGROUND: Introduction of Halyomorpha halys (Stål) in the USA has disrupted many established integrated pest management programs for specialty crops, especially apple. While current management heavily relies on insecticides, one potential alternative tactic is attract‐and‐kill (AK), whereby large numbers of H. halys are attracted to and retained in a circumscribed area using attractive semiochemicals and removed from the foraging population with an insecticide. The goal of this study was to evaluate if AK implementation in commercial apple orchards can result in levels of H. halys damage that are equal to or less than those from grower standard management programs. RESULTS: Over 2 years at farms in five Mid‐Atlantic USA states, we found that the use of AK resulted in 2–7 times less damage compared with grower standard plots, depending on year and period. At selected trees on which AK was implemented, over 10, 000 H. halys individuals were killed in two growing seasons, and the use of AK reduced the crop area treated with insecticide against H. halys by 97%. Using AK had no impact on the natural enemy or secondary pest community over the same period. CONCLUSIONS: Overall, the use of AK was effective at managing low to moderate H. halys populations in apple orchards, but must be optimized to increase economic feasibility for grower adoption. © 2018 Society of Chemical Industry Abstract : We evaluated whether attract‐and‐kill could manage the threat posed by Halyomorpha halys in apple orchards. Low to moderate populations were controlled, but this approach must be optimized for economic feasibility.